TEACHERS' PERCEPTION GRADING PRACTICE SCALE (TPGPS) ADAPTATION - Fadillahi Arief; Farah Aulia (RADJA PUBLIKA, 2026)
This study aims to adapt and conduct initial validation of the Teachers' Perceptions of Grading Practices Scale (TPGPS) into Indonesian. This scale measures teachers' perceptions of assessment practices in six components, namely interests, benefits, student efforts, student abilities, teachers' assessment habits, and perceived self-efficacy from the assessment process. Participants consisted of 130 high school teachers who completed the questionnaire online. Data were analyzed using Confirmatory Factor Analysis (CFA) using JAMOVI version 2.3.28 to assess the model suitability of the six-factor structure. The results showed acceptable model conformity with RMSEA = 0.0361 (≤ 0.08), although the values of CFI (0.775) and TLI (0.758) were slightly below the recommended threshold (≥ 0.90). The reliability of such scales is high (α Cronbach = 0.827), which indicates good internal consistency. Some items with low factor loading are recommended for revision at the later stages of validation. Overall, the Indonesian version of TPGPS is valid and reliable for assessing teachers' perceptions of assessment practices in the context of education in Indonesia.